2010
DOI: 10.1111/j.1365-2141.2010.08417.x
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic haematopoietic stem cell transplantation for myelofibrosis: a report of the Société Française de Greffe de Moelle et de Thérapie Cellulaire (SFGM‐TC)

Abstract: SummaryAllogeneic haematopoietic stem-cell transplantation (HSCT) is the only curative treatment for myelofibrosis. We report an analysis of the Société Française de Greffe de Moelle et de Thérapie Cellulaire (SFGM-TC) registry including patients with myelofibrosis transplanted between 1997 and 2008. Potential risk factors affecting engraftment, non-relapse mortality (NRM), overall survival (OS) and progression-free survival (PFS) were analysed. One hundred and forty-seven patients, aged 20-68 (median 53) year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 22 publications
8
75
1
5
Order By: Relevance
“…36,83 Interestingly, a French study noted a favorable survival for male patients who underwent pretransplant splenectomy, while a German study demonstrated a higher relapse rate in the splenectomized patients. 17,84 In addition, there appears to be no agreement as to the actual size of the spleen which might, or might not, serve as a trigger for pretransplant therapy. There is now an emerging consensus to avoid splenic irradiation or splenectomy immediately prior to transplant due to the intrinsic complications of radiation and splenectomy and thus the notion of reducing splenomegaly medically is indeed attractive.…”
Section: Impact Of Targeting the Jak/signal Transducers And Activatormentioning
confidence: 99%
“…36,83 Interestingly, a French study noted a favorable survival for male patients who underwent pretransplant splenectomy, while a German study demonstrated a higher relapse rate in the splenectomized patients. 17,84 In addition, there appears to be no agreement as to the actual size of the spleen which might, or might not, serve as a trigger for pretransplant therapy. There is now an emerging consensus to avoid splenic irradiation or splenectomy immediately prior to transplant due to the intrinsic complications of radiation and splenectomy and thus the notion of reducing splenomegaly medically is indeed attractive.…”
Section: Impact Of Targeting the Jak/signal Transducers And Activatormentioning
confidence: 99%
“…No significant difference was observed in OS and NRM between patients with standard myeloablative and reduced-intensity regimens, which is also compatible with the results of previous reports. 23 tensity regimens (46%) is increased compared with that of those prepared by myeloablative conditioning (15%), approaching significance (P 0.06). 17 Therefore, allo-SCT with reduced-intensity conditioning could be the potential treatment of choice for MF patients who are not eligible for myeloablative conditioning and should be carefully chosen for younger MF patients, considering its association with a higher risk of relapse compared with myeloablative conditioning.…”
Section: Discussionmentioning
confidence: 82%
“…In univariate analysis, lower platelet count ( 10 10 4 / l) at transplantation and previous transformation into AML were associated with poor OS; these findings are consistent with those of a previous report. 23 Furthermore, lower platelet count at transplantation was significantly associated with TTP, which suggested that patients with a lower platelet count at transplantation were more likely to suffer a relapse after allo-SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most MPN evolve to AML through a myelofibrosis step, engraftment was not a major concern and could be achieved in the majority of patients (>90%). 9,18 Moreover, TRM was relatively moderate,~22%, suggesting the feasibility of the procedure. The main cause for the poor outcome in our study was a high incidence of relapse.…”
Section: Discussionmentioning
confidence: 98%